2019
DOI: 10.3390/plants8030059
|View full text |Cite
|
Sign up to set email alerts
|

Ginger and Turmeric Essential Oils for Weed Control and Food Crop Protection

Abstract: Ginger and turmeric are two food ingredients that are in high demand due to their flavor and positive effects on health. The biological properties of these spices are closely related to the aromatic compounds they contain. The chemical compositions of their essential oils and their in vitro phytotoxic activity against weeds (Portulaca oleracea, Lolium multiflorum, Echinochloa crus-galli, Cortaderia selloana, and Nicotiana glauca) and food crops (tomato, cucumber, and rice) were studied. Forty-one compounds, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…), considered one of the world’s worst weeds infesting cropping systems [ 232 ], especially detrimental in rice paddies, where it interferes with canopy light transmission, triggering a series of metabolic alterations in rice that can lead to severe losses of even 55.2% [ 233 ]. Concretely, it reduced the hypocotyl development of the three weeds 56.55%, 40.45% and 39.33%, respectively, from 0.125 to 1 µL/mL, without affecting either the seed germination or the hypocotyl growth of the tomato, cucumber and rice crops [ 234 ] ( Table 3 ).…”
Section: Potential Applications Of C Longa Essmentioning
confidence: 99%
See 1 more Smart Citation
“…), considered one of the world’s worst weeds infesting cropping systems [ 232 ], especially detrimental in rice paddies, where it interferes with canopy light transmission, triggering a series of metabolic alterations in rice that can lead to severe losses of even 55.2% [ 233 ]. Concretely, it reduced the hypocotyl development of the three weeds 56.55%, 40.45% and 39.33%, respectively, from 0.125 to 1 µL/mL, without affecting either the seed germination or the hypocotyl growth of the tomato, cucumber and rice crops [ 234 ] ( Table 3 ).…”
Section: Potential Applications Of C Longa Essmentioning
confidence: 99%
“…Among them, C. selloana exhibited a special sensitivity to C. longa essential oil. The seed germination was drastically inhibited in a dose-dependent manner, achieving 81.71% of reduction at the highest dose (1 µL/mL) applied [ 234 ] ( Table 3 ). It is interesting to note that the management of invasive species with sustainable alternatives is another important step in global agriculture, because these species are becoming naturalized in a wide number of areas with serious consequences: they influence the environment, change soil properties, affect diversity, etc.…”
Section: Potential Applications Of C Longa Essmentioning
confidence: 99%
“…Bigdoli et al reported that the Rosmarinus officinalis essential oil may influence metabolic pathways in such a way that it can limit the interactions between plant and beneficial bacteria, producing an ineffective performance in plant growth promotion and disease management [29]. Ibanez and Blazquez found out that the active components of essential oils of ginger (α-zingiberene (24.9±0.8%), β-sesquiphelladrene (11.7±0.3%), ar-curcumene (10.7±0.2%), and β-bisabolene (10.5±0.3%)), and the active components of turmeric oil (ar-turmerone (38.7±0.8%), β-turmerone (18.6±0.6%), and α-turmerone (14.2±0.9%)) caused weed decay without producing phytotoxic effects in the crops [30]. While the majority of these studies target the germination stage of weeds [31], it is important to note that the effects of the application of essential oils goes far beyond the herbicidal effects into the preservation of the normal beneficial soil microbial activity, especially desirable for organic agricultural production.…”
Section: Applications Of Essential Oils In Agriculturementioning
confidence: 99%
“…The Etlingera species are infamous for their high content of secondary metabolites such as saponins, flavonoids, tannins, alkaloids, terpenoids, and many other bioactive compounds [8,9]. These bioactive compounds are reported to exert allelopathic effect that retarded the growth of the several weed species, as conducted by Ibáñez and Blázquez [10]. These studies also revealed that the bioactive compounds released by members of the Zingiberaceae family shall have adverse effects on neighbouring plants, affecting the growth and development of other plants including crops.…”
Section: Introductionmentioning
confidence: 99%